When the patient fails to respond to treatment: myasthenia gravis. - Hilton-Jones, D (2007)
Myasthenia gravis is one of the most satisfying neurological disorders to treat. There are few other conditions in which therapeutic intervention can take a patient from being bed-bound and ventilated to normality. Most patients present with less severe symptoms, but even mild extraocular muscle weakness can be profoundly disabling. The standard therapeutic approach is successful for most patients, which can make the non-specialist neurologist somewhat blasé about its management. However, panic can set in when the standard approach fails. Failure is often the result of incorrect diagnosis, or inappropriate use of first-line treatments. This article outlines the main reasons for failure and gives advice on alternative therapeutic strategies.